Розумна тростина для слабозорих на базі Arduino Nano - Жигалкін, Є. В. (ХНУРЕ, 2024)
Computers are ubiquitous in our lives, but microcontrollers, often overlooked, are essential in powering many devices beyond smartphones. This document presents the development of a Smart Cane system utilizing Arduino technology to assist blind individuals in navigating their surroundings safely. The system integrates ultrasonic distance sensors and light sensors to detect obstacles and be visible in the dark. Controlled by an Arduino microcontroller, the Smart Cane provides real-time feedback through haptic alerts. This innovative solution enhances the mobility and safety of visually impaired individuals, offering potential for further refinement and expansion in future versions.
Keywords: тростина для слабозорих; Arduino Nano